Synthesis and Antimicrobial Evaluation of Some New 2-(5,6-Dihydro-4H-1,2,4-triazolo[4,3-a]benz[F]azepin-1-yl)methyl)-4-substituted Phthalazin-1(2H)-ones - E. El-Shamy, Ibrahim; Abdel-Mohsen, A.M.; M.G. Fouda, Moustafa; S. Al-Deyab, Salem; Abdel-Megeed, Ahmed; A. El-Hashash, Maher (Asian Journal of Chemistry, 2014)
Starting from 4-substituted-phthalazin-1(2H)-one (1), A series of new 2-(5,6-dihydro-4H-1,2,4-triazolo[4,3-a]benz[f]azepin-1-yl)methyl)-4-substituted phthalazin-1(2H)-ones derivatives (5) have been synthesized. The structure of synthesized new compounds was established by spectral data and screened for their antimicrobial activities against various bacteria and fungi strains.